Adubação com silício e tolerância ao déficit hídrico em cana-de-açúcar - Bezerra, Breno Kennedy Lima [UNESP] (2015)
Although the Brazilian sugar and ethanol industry has been facing one of its worst crises, sugarcane crop has been expanding to new areas, including sandy soils subject to water deficit. Silicon (Si) is an element that can minimize the effects of drought in several plants, but there is little information on its effects on sugarcane subjected to water deficit. Thus, the objective of this study was to evaluate the use of silicon fertilization in two sugarcane cultivars under water deficit during phase (tillering and maximum development). The two experiments were carried out inside a greenhouse at Agency for Agribusiness Technology of São Paulo (APTA), Piracicaba, SP, where were transplanted pre-sprouted seedlings in pots of 100 L. The design was randomized blocks with triple factorial 2x2x2 (variety, silicon and water regime) with four replications. Two varieties of sugarcane (drought tolerant -RB867515 and as sensitive-RB855536), with and without silicon-supplied (600 and 0 kg ha-1) subjected or not to water restriction (60% and 100% humidity of field capacity, respectively) this condition was imposed for 30 and 60 days during the tillering phase or maximum development phase (three and six months after transplanting) were studied. Evaluations were done at three periods: before water deficit and after 30 and 60 days. The effects in biochemical attributes (plant height, number of tillers, total leaves and green leaves) and physiological (SPAD index, electrolyte leakage, chlorophyll a and b content, specific leaf mass, leaf relative water content and leaf water potential) were studied. Si increased morphological development, by increasing on number of total leaves and tillers during tillering phase and increasing on number of total leaves, tillers and plant height on maximum development phase, on both varieties. There was effect of ...